Tuberculin skin testing among healthcare workers in the University of Malaya Medical Centre, Kuala Lumpur, Malaysia - Tan, L.H.; Kamarulzaman, A.; Liam, C.K.; Lee, T.C. (2002)
To determine the occupational risk of Mycobacterium tuberculosis infection among healthcare workers (HCWs) and to examine the utility of tuberculin skin testing in a developing country with a high prevalence of bacille Calmette-Guerin vaccination. DESIGN: Tuberculin skin test (TST) survey. SETTING: A tertiary-care referral center and a teaching hospital in Kuala Lumpur, Malaysia. PARTICIPANTS: HCWs from medical, surgical, and orthopedic wards. INTERVENTION: Tuberculin purified protein derivative RT-23 (State Serum Institute, Copenhagen, Denmark) was used for the TST (Mantoux method). RESULTS: One hundred thirty-seven (52.1) and 69 (26.2) of the HCWs tested had indurations of 10 mm or greater and 15 min or greater, respectively. Medical ward HCWs were at significantly higher risk of a positive TST reaction than were surgical or orthopedic ward HCWs (odds ratio, 2.18; 95 confidence interval, 1.33 to 3.57; P = .002 for TST positivity at 10 mm or greater) (odds ratio, 2.61; 95 confidence interval, 1.44 to 4.70; P = .002 for TST positivity at 15 mm or greater). A previous TST was a significant risk factor for a positive TST reaction at either 10 mm or greater or 15 min or greater, but a duration of employment of more than 1 year and being a nurse were only significantly associated with a positive TST reaction at a cut-off point of 15 min or greater. CONCLUSIONS: HCWs at the University of Malaya Medical Centre had an increased risk for M. tuberculosis infection that was significantly associated with the level of occupational tuberculosis exposure. A TST cut-off point of 15 min or greater may correlate better with M. tuberculosis infection than a cut-off point of 10 min or greater in settings with a high prevalence of bacille Calmette-Guerin vaccination.